Justice for the Poor: An Analysis of the Right to Access to Justice and Free Legal Aid Centers - García Westphalen, Luis (2025)
In a constitutional State governed by the rule of law, access to justice entails a service obligation on the part of the State: to provide judicial administration services and free public defense, especially for people living in poverty. Within this framework, this paper analyzes whether the Free Legal Aid Program (Alegra) of Peru’s Ministry of Justice and Human Rights (MINJUSDH) guarantees the availability, accessibility, and quality of justice services. To this end, it examines the location of Alegra centers, the workload at each center, current protocols, and other management documents obtained through requests for access to public information. It concludes that there is an almost total absence of Alegra services in provinces with the highest percentage levels of poverty. There is also a lack of Alegra services in most provinces with the largest numbers of people living in poverty. Other findings reveal accessibility barriers for persons with disabilities; inadequate distribution of financial and human resources (which generates overload in the legal sponsorship of judicial proceedings and compromises the quality of service); inefficiencies in verifying the poverty status of service users; and a serious conflict of interest on the part of MINJUSDH authorities responsible, on the one hand, for administering the legal defense of individuals accused of alleged crimes and, on the other hand, for managing the legal defense of crime victims. The study argues that, in order to guarantee effective access to justice, institutional reorganization is required, along with improved resource allocation and the implementation of transparency mechanisms in service management.